Impact Of Covid-19 On Construction Industry From Contractor’s Perspective - Radzi, Fatin Nadia Mohamad (Universiti Sains Malaysia, 2021)
World Health Organization (WHO) has declared coronavirus disease of 2019 (COVID-19) a pandemic following the spread of this novel virus across the globe. This pandemic affected not only human health but also the operational health of businesses and organisations, the construction industry inclusive. The Covid-19 is a pandemic issue that is causing widespread global disruption forcing lockdowns in many countries including Malaysia as an effort in disconnecting the virus from spreading. As an initiative, the Malaysian government has call for the Movement Control Order (MCO) as one of the lockdown alternatives starting on 18th March 2020. Due to that, the MCO has given a huge impact on Malaysia’s industries including the construction industry. Hence, to successfully deliver projects, time and cost become essential components which in this current scenario, most of the on-going projects declined to deliver the project according to the time and cost as planned. Thus, this study intends to explore the contractor perception on how they face this lockdown specifically in Pulau Pinang, Malaysia. Hence, the method adopted to get the data was by distribution of questionnaire to contractor’s company. Results from the questionnaire found that the MCO has resulted in 6 main impacts which consists of regulation compliance, safety, additional time for project delivery, increase in development cost, limited human resources supplies and limited resource availability on-site. These results show that the MCO has given the negative impact on project success. This is important for the government to ensure their awareness on the consequences of the MCO towards the construction industry and facilitate the construction players to overcome the six factors mentioned in this paper.